2014
DOI: 10.1007/s10753-014-9907-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Salivary Matrix Metalloproteinases, Neutrophil Elastase, Myeloperoxidase in Patients with Chronic or Aggressive Periodontitis

Abstract: Salivary, serum matrix metalloproteinase-8 (MMP-8), tissue inhibitor of matrix metalloproteinases-1 (TIMP-1), neutrophil elastase (NE), and myeloperoxidase (MPO) levels were investigated in generalized chronic periodontitis (GCP), generalized aggressive periodontitis (GAgP), and healthy groups. Whole-mouth clinical periodontal measurements were recorded. Salivary, serum concentrations of MMP-8, MPO, TIMP-1, and NE were determined by immunofluorometric assay or ELISA in 18 patients with GCP, 23 patients with GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
5
39
2
2
Order By: Relevance
“…The current results are in line with reported increased levels of MMP‐8 in saliva from patients with periodontitis, 30,37 as well as in GCF from children with AgP 38 . On the other hand, Nizam et al 39 did not find significant differences in MMP‐8 levels in serum or saliva between patients with AgP and healthy patients, which could be at least partially related to the higher age in healthy patients. Also, the former study used an immunofluorometric assay, which may differ in the sensitivity and ability to detect active forms of MMP‐8 40 compared with the current analysis, which could also account for the contradictory results.…”
Section: Discussionsupporting
confidence: 91%
“…The current results are in line with reported increased levels of MMP‐8 in saliva from patients with periodontitis, 30,37 as well as in GCF from children with AgP 38 . On the other hand, Nizam et al 39 did not find significant differences in MMP‐8 levels in serum or saliva between patients with AgP and healthy patients, which could be at least partially related to the higher age in healthy patients. Also, the former study used an immunofluorometric assay, which may differ in the sensitivity and ability to detect active forms of MMP‐8 40 compared with the current analysis, which could also account for the contradictory results.…”
Section: Discussionsupporting
confidence: 91%
“…Myeloperoxidase has been shown to be elevated in inflammatory periodontal sites [32]. It was suggested that MPO could be regarded as an indicator of increased risk for local and systemic inflammation such as periodontal tissue destruction or as an early sign of atherosclerosis [33]. The present results showed that statins might have a local antioxidant efficacy demonstrated with low levels of MPO.…”
Section: Discussionsupporting
confidence: 52%
“…9 MMPs and TIMPs are also produced locally in periodontium and altered levels of MMPs are associated with inflammation related with gingivitis and periodontitis. 10,11 MMP-8 is a proteolytic enzyme secreted mainly by neutrophils that is present in inflamed gingiva, gingival crevicular fluid (GCF), saliva and serum. MMP-8 can be activated both by host and bacterial enzymes.…”
Section: Introductionmentioning
confidence: 99%